Pengaruh Online Customer Review dan Rating terhadap Keputusan Pembelian Shopee di Kota Semarang - Hidayat Bagas Ramadhan; Heru Sulistyo (Lembaga Yasin AlSys, 2026)
The growth of e-commerce has driven significant changes in consumer behavior, particularly in purchase decision-making that increasingly relies on digital information such as online customer reviews and online customer ratings. This study aimed to analyze the influence of online customer reviews and online customer ratings on purchase decisions on the Shopee platform in Semarang City, with e-trust as a moderating variable. A quantitative approach with an explanatory research design was employed, with data collected through questionnaires from 100 respondents who had shopped on Shopee, selected using purposive sampling. Data were analyzed using the Partial Least Squares (PLS) method with SmartPLS 4 software. The results show that online customer reviews have a positive and significant effect on purchase decisions, whereas online customer ratings do not have a significant effect on purchase decisions. In addition, e-trust does not moderate the influence of either online customer reviews or online customer ratings on purchase decisions. These findings indicate that consumers place greater emphasis on the quality of review information than on numerical ratings alone when making purchase decisions. In conclusion, informative and credible reviews play a crucial role in encouraging consumer purchase decisions, with practical implications for sellers and e-commerce platforms to enhance review quality and information transparency in order to strengthen consumer trust and shopping experience.